(Res)significações religiosas no sertão das gerais: as folias e os reis em Januária (MG) - 1961/2012 - Correia, Iara Toscano (2013)
The speeches assumed by modernity have been treating the popular culture themes as a political correctness showcase, capable of solve latent economic problems. Such speeches defend the increment of craft production, the viability of festivals and popular traditions and the folklore in general, as a way to meet the virtual touristic and market demand and, at the same time, promote the sustainable development of rural and urban communities. Reflecting about this interest in what is popular and marginal at the beginning of this century, we turn our eyes to the follies of kings microcosm at the mining town of Januária, on the banks of Rio San Francisco. We chose as basis of observation four distinct groups of kings: the Folia de Reis dos Figueiredos, the Folia de Reis do Alegre, the Folia de Reis do Zé Preto, and Terno de Reis dos Temerosos. Our starting point was the folkloric survey conducted by the National Campaign for Protection of Folklore, in 1961, for the city s centenary of the founding celebration. The study is structured into two analytical movements: first, from a diachronic perspective about the ritual, we identify the permanencies, ruptures and (re)significations occurred in the tradition of kings of this region; in the second moment, we reflect about the institutional appropriation of themes linked to the popular universe, as well as the creation of local folkloric fairs and festivals, and the interactions and tactics used by the kings suits to maintain their traditions in face of the growing interest in their practices at this passage millennium.